Penanaman Karakter Siswa Melalui Pembelajaran PAI pada Siswa Kelas IV SD Muhammadiyah 16 Surakarta Tahun 2015 - Fitriyanti, Naziro; , Dra. Ratnasari Diah Utami, M.Si., M.Pd; , Murfiah D. W, MPsi (2015)
This study aimed to describe: 1) The values of Islamic education that was developed in the cultivation of character in the fourth grade students of SD Muhammadiyah Surakarta 16. 2) The planting of character in students through learning PAI fourth grade 16 Surakarta Muhammadiyah. 3) inhibiting factors in the cultivation of character in students through learning in fourth grade PAI 16 Surakarta Muhammadiyah. This type of research is qualitative research (Qualitative Research) .Informan this research is the principal, teachers and students of class IV PAI. Data collection techniques used were observation, interviews, and documentation. Data were analyzed through the steps of data reduction and conclusion. Mechanical data validity checking is done by triangulation of sources and techniques. The results showed that in SD Muhammadiyah 16 Surakarta has implemented the planting of character in students with methods of habituation and exemplary through learning PAI, a method of habituation and exemplary penananaman characters in 16 Surakarta already well underway, although there was little resistance, but the teacher has given a solution so that these obstacles can be minimized.